Long-term relationships between summer clouds and aerosols over mid-high latitudes of the Northern Hemisphere - Watari, Akihisa; Iizuka, Yoshinori; Fujita, Koji; Masunaga, Hirohiko; Kawamoto, Kazuaki (Scientific Reports, 2024)
While the short-term relationship between clouds and aerosols is well known, no adequate data is available to verify the longer-term, annual to decadal, relationship. It is important to quantify the aerosol–cloud interaction (ACI) for mitigating uncertainty in climate prediction. Here the long-term ACI over the mid-to-high latitudes of the Northern Hemisphere was analyzed by using seasonally-resolved ion fluxes reconstructed from a southeastern Greenland ice core (SE-Dome ice core) as aerosol proxies, and satellite-based summer cloud amount between 1982 and 2014. As a result, SO 4 2− flux in the ice core shows significant positive correlation with total cloud amounts ( CC T ) and cloud droplet concentration ( N d ) in the summer over the southeastern Greenland Sea, implying that the sulfate aerosols may contribute to the variability of CC T via microphysical cloud processes. Significant positive correlations are persistent even under the constrained conditions when cloud formation factors such as relative humidity, air temperature at cloud height, and summer North Atlantic Oscillation are limited within ± 1σ variability. Hence sulfate aerosols should control the interannual variability of summer CC T In terms of decadal changes, CC T was approximately 3–5% higher in the 1960s–1970s than in the 1990s–2000s, which can be explained by changes in the, SO 4 2 - flux preserved in the SE-Dome ice core.